If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + 16 + -1x = 16 Combine like terms: -17 + 16 = -1 -1 + -1x = 16 Solving -1 + -1x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 16 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 16 + 1 -1x = 16 + 1 Combine like terms: 16 + 1 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| 2y-x=y-5 | | 0.25+.05=6.10 | | 5b^2-22b-15=0 | | 18+8t=9(t-2) | | 3h-12=11h+4 | | 8(-9-2+3v-6v)= | | 2(4)-y=2 | | -6x-4(-7x-13)=58 | | 2(3)-y=2 | | y+2.6=6.9 | | 4x-22=54 | | -n-5(-6-7)=-119 | | 4x^2+20x+25=64 | | -9(1+6+6v)= | | 100=x+(x+2) | | 4h-4=8 | | 61.94+56.06-x-45=38 | | -3(-2+9v)= | | -16t^2+18t+10=0 | | -7(n-5)-6n=4n+1 | | 6(2x+3)=11x-3-6x | | 2x^2+10y=-7 | | 11b+3=25 | | t^2-16t+64= | | (2z+1)+9=(6z-9) | | 11=1-7x-3x | | 8t^2+9t+5=0 | | 0.26=-2.5(76-4) | | 5n-11=2n+2 | | 7r^2-2r=0 | | n+6n=-14 | | 4x^2-2x^2+1=0 |